Estudo de evento de retornos anormais em IPO na B3 nos anos de 2016 a 2021 - Sacchi, Fernando Henrique (2024)
The study aims to analyze the phenomena of underpricing and underperformance in shares of companies that went public on the stock exchange, the so-called Initial Public Offering (IPO). The event study methodology was used in a sample composed of 86 companies that went public on the Brazilian stock exchange in the period from 2016 to 2021. The topic has strong relevance due to the fact that a significant number of companies went public in the years 2020 and 2021, moving a significant amount of resources. 74 companies debuted on the stock exchange during this period, in 2021 alone there were 46 companies going public and a turnover of R$126.9 billion. The companies' quotation returns on the first day of trading and in a period of 6, 12 and 24 after the IPO. Abnormal returns were calculated by comparing the sample returns with market returns, in this case the IBOVESPA index, widely used in the literature on the subject. Significant abnormal returns were obtained for the first day in the amount of 4.97% and 5.62%, characterizing the phenomenon of underpricing. Furthermore, the phenomenon of underperfomance was observed at the end of the 24th month of trading, with the average accumulated abnormal returns being equal to -34.87% and -38.95%, excluding the return on the first day. The results are in line with what is widely documented in the literature on the subject.